AB0349 DISEASE ACTIVITY IN RHEUMATOID ARTHRITIS AND RISK OF LUNG INVOLVEMENT. (June 2019) - Saidane, Olfa; Gafsi, Leila; Sahli, Hana; Tekaya, Aicha Ben; Tekaya, Rawdha; Mahmoud, Ines; Abdelmoula, Leila
Abstract : Background: Rheumatoid arthritis (RA) is a common inflammatory disease developing within joints but extra-articular organs such as the lung could be involved. Objectives: To determine the relationship between disease activity and lung involvement in rheumatoid arthritis (RA) Tunisian patients. Methods: We performed a retrospective study of patients with RA diagnosed according to American College of Rheumatology-European League Against Rheumatism classification criteria for RA 2010 between 2014 and 2017 in a department of rheumatology in the north of Tunisia. The prevalence of pulmonary involvement was determined based on combined results from chest-X-ray, computed tomography of the chest and pulmonary functional tests. Disease activity was evaluated based on number of night waking, morning stiffness duration, painful joints number and swelling joints number, erythrocytes sedimentation rate (ESR) and C-reactive protein levels (CRP). Specific disease activity scores were also noted including the 28-joint Disease Activity Score Index (DAS28), Clinical Disease Activity Index (CDAI) and Simplified Disease Activity Index (SDAI). Results: Sixty five patients were collected. Mean age was 56 years ± 12.8 years and mean age of disease onset was 46.4 ± 13.8 years ranging from 17 to 75 years. Mean disease duration was 9.6 ±10.1 year ranging from 1 to 38 years. Number of painful joints was 13.71 at mean and swelling joints number was 5.98. Morning stiffness duration was 1.03 hour at mean and number of night waking was 2.31. Concerning laboratory investigations, mean ESR was 49.7 mm ant mean CRP level was 13.6 mg/l. The average of DAS28 was 5.8. The overall frequency of lung involvement based on different lung investigations was 27.6% (18 patients). Interstitial lung disease was found in 7 cases, bronchiectasis was found in 5 cases, rheumatoid nodule in 4 cases and pleural disease in 2 cases. Patients with lung involvement had significantly higher painful joints number (p=0, 034) and no difference was seen concerning swelling joints number. Number of night waking and morning stiffness duration had no impact in lung involvement (p=0, 651, p=0, 907 respectively). RA patients with lung involvement displayed higher ESR level (p=0, 032) and no difference was seen concerning CRP level. No association was found between lung involvement and specific disease activity scores (DAS28, CDAI, SDAI). Conclusion: Our study showed that only high level of ESR could be associated with lung involvement in RA Tunisian patients. References: [1] Pérez-Doramea R, Mejiaa M, Mateos-Toledoa H, Rojas-Serranob J.Rheumatoid arthritis-associated interstitial lung disease: Lung inflammation evaluated with high resolution computed tomography scan is correlated to rheumatoid arthritis disease activity. Clin Rheumatol. 2015;11(1):12-6. [2] Jearn LH, Kim TY. Level of anticitrullinated peptide/protein antibody is not associated with lung diseases in rheumatoid arthritis. J Rheumatol 2012;39:1493-4.2] Jearn LH, Kim TY. Level of anticitrullinated peptide/protein antibody is not associated with lung diseases in rheumatoid arthritis. J Rheumatol 2012;39:1493-4. Disclosure of Interests: None declared